DNA methylation of ICAM4 and NOXO1 participate in the formation of uterine fibroids via regulating immune cell infiltration: ICAM4 and NOXO1: Uterine fibroid formation - Zhu, Yafei; Shi, Wei; Han, Wenling; Wang, Maohuai; Chen, Jie; Zhou, Jieli (Cellular and Molecular Biology, 2023)
This atudy aimed to reveal the effect of DNA methylation on immune infiltration of uterine fibroids (UFs) and to further classify UFs based on transcriptomic characteristics. The transcriptome and DNA methylation data of UFs were collected from the GEO database. After taking the intersection of the differentially expressed genes in these two types of data, the intersection gene was used to draw ROC curves and to filtrate the candidate genes with AUC≥0.8. Immune infiltration analysis was performed in the online tool EPIC. The correlation between gene with AUC≥0.8 and the abundance of each immune cell type was calculated with |R|>0.3 and P<0.05. ConsensusClusterPlus package in R software was used to further cluster the samples of UFs. In this study, a total of 41 RNA-seq data (10 normal uterine samples and 31 UFs samples) and 34 DNA methylation data (10 from normal subjects and 24 from patients with UFs) were involved. The significantly down-regulated ICAM4, SPECC1L, and NOXO1 were the top three methylated drive genes of UFs. Therefore, NOXO1 and ICAM4 present an intimate correlation to immune cell infiltration. Besides, UFs could be clustered into two subtypes, including a TSAB1 up-regulated subtype and a FOSB up-regulated subtype. DNA methylation of ICAM4 and NOXO1 are involved in the pathogenesis of UFs via regulating immune cell infiltration. Further classification based on transcriptomic characteristics could divide UFs into sexual steroids-related and biomechanics-related subtypes, which would promote its non-invasive treatment.